Self-efficacy in idiopathic inflammatory myopathies: associated factors, profiles, and patient-reported outcomes - Praggya Yaadav; Lekshmi M Rahulan; Suhana Hussain; Manali Sarkar; Vincenzo Venerito; Vahed Maroufy; Maria R Pellico; Anne-Marie Russell; Sreoshy Saha; Elena Nikiphorou; Ioannis Parodis; Vidya S Limaye; et al. (Rheumatology, 2026)
Abstract Objectives Self-efficacy (SE) is central to chronic disease self-management but remains poorly characterized in idiopathic inflammatory myopathies (IIMs). We aimed to identify factors associated with SE, characterize SE profiles, and examine associations with patient-reported outcomes (PROs) in IIMs. Methods Cross-sectional data from 5,802 participants across IIMs, other rheumatic diseases (RMDs), and non-rheumatic autoimmune diseases (nRAIDs) were analyzed. SE was measured using the Self-Efficacy for Managing Chronic Disease (SEMCD) scale. Hierarchical regression identified factors independently associated with SE, and k-means clustering defined SE-health profiles. Associations with PROs were examined in a separate multivariable model. Results IIM patients had lower SE (median SEMCD 5.3) than RMDs (5.8) and nRAIDs (6.5), with confidence lowest for managing fatigue and physical discomfort. In the fully adjusted integrated model (R²=0.222), mental health comorbidity (B=-0.898) and financial difficulty (B=-0.734) were most strongly associated with lower SE, while regular exercise (B = 0.770) and family support (B = 0.150) were associated with higher SE. The PRO model explained 48.3% of SE variance (R²=0.483); resilience was the strongest positive association, while fatigue and pain were negatively associated. Four SE-health profiles were identified, including a clinically distinctive resilient-despite-burden subgroup (24%) with high symptom burden but preserved SE and mental health. Higher SE was associated with better physical and mental health, greater resilience and life satisfaction, and lower fatigue, pain, and loneliness (all p < 0.001). Conclusion SE in IIMs is associated with modifiable socioeconomic and psychological factors and with better health outcomes. Profile-based stratification may help identify vulnerable subgroups and guide targeted interventions.